Uncovering regional inequalities in digitalization : a multifaceted measurement for Germany - Detemple, Jonas [Verfasser]; Wicht, Alexandra [Verfasser] (My University, 2024)
„The ongoing global digital transformation has significant implications for economies and societies, with potential benefits and challenges. This study addresses the critical need for a comprehensive measurement of regional digitalization in Germany to better understand its impact on various aspects of life, including education, employment, and working conditions. Using confirmatory factor analysis (CFA), it introduces a multifaceted regional digitalization measure at the administrative district level (NUTS-3) that incorporates digital infrastructure, culture, technology capacity, high-tech human capital, and digitalization-related innovativeness. Results for 2013 and 2017 are compared. The study reveals that digitalization varies significantly across regions, but hardly over time. Urban regions tend to have higher digitalization levels, which are positively associated with economic productivity and high-skilled labor demand. Our developed measurement of regional digitalization is publicly available.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.1.4 Regionalisierung; 370; 330; 600; Arbeitswelt; Bildungssystem; Gesellschaft; Digitalisierung; Regionale Disparität; Landkreis; Faktorenanalyse